Exclusive J/ψ and ψ(2S) production in pp collisions at √s = 7 TeV - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Journal of physics. G, Nuclear and particle physics, 2013)
Exclusive J/ψ and ψ(2S) vector meson production has been observed in the dimuon channel using the LHCb detector. The cross-section times branching fractions to two muons with pseudorapidities between 2.0 and 4.5 are measured to be where the first uncertainties are statistical and the second are systematic. The measurements are found to be in good agreement with results from previous experiments and theoretical predictions. The J/ψ photoproduction cross-section has been measured as a function of the photon-proton centre-of-mass energy. The results are consistent with measurements obtained at HERA and confirm a similar power law behaviour for the photoproduction cross-section.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 23.04.2021